Smart Shopping Trolley - Vinoth Kumar, L.; Poornima, B.; Nithusiga, S.; Anitha valli, R. (International Research Journal of Engineering and Technology (IRJET), 2020)
This paper targeted to reduce the Queue at a billing counter in a shopping complex. The system does the same by displaying the price of the product inside the cart. In this way the customer can directly pay the amount at the billing counter and leave with the commodities he/she has bought. It eliminates the traditional scanning of products at the counter and in turn speeds up the entire process of shopping, also with this system the customer shall know the total amount to be paid and hence can accordingly plan his shopping by only buying the essential commodities resulting in enhanced savings. Since the entire process of billing is automated it reduces the possibility of human error substantially. Also the system has a feature to delete the scanned products to further optimize the shopping experience of the customer. The hardware for the test run is based on the Arduino platform and zigbee modules, as both are very popular in small-scale research and wireless automation solution. Also the amount can be paid through online using QR code scanner.
Keywords: Microcontroller; RFID Reader; Zig bee; ESP8266; LCD Display